Who Benefits From Hip Arthroplasty or Knee Arthroplasty? Preoperative Patient-reported Outcome Thresholds Predict Meaningful Improvement - Langenberger, Benedikt; Steinbeck, Viktoria; Busse, Reinhard (Clinical orthopaedics and related research, 2024)
Hip arthroplasty (HA) and knee arthroplasty (KA) are high-volume procedures. However, there is a debate about the quality of indication; that is, whether surgery is truly indicated in all patients. Patient-reported outcome measures (PROMs) may be used to determine preoperative thresholds to differentiate patients who will likely benefit from surgery from those who will not. (1) What were the minimum clinically important differences (MCIDs) for three commonly used PROMs in a large population of patients undergoing HA or KA treated in a general orthopaedic practice? (2) Do patients who reach the MCID differ in important ways from those who do not? (3) What preoperative PROM score thresholds best distinguish patients who achieve a meaningful improvement 12 months postsurgery from those who do not? (4) Do patients with preoperative PROM scores below thresholds still experience gains after surgery? Between October 1, 2019, and December 31, 2020, 4182 patients undergoing HA and 3645 patients undergoing KA agreed to be part of the PROMoting Quality study and were hence included by study nurses in one of nine participating German hospitals. From a selected group of 1843 patients with HA and 1546 with KA, we derived MCIDs using the anchor-based change difference method to determine meaningful improvements. Second, we estimated which preoperative PROM score thresholds best distinguish patients who achieve an MCID from those who do not, using the preoperative PROM scores that maximized the Youden index. PROMs were Hip Disability and Osteoarthritis Outcome Score-Physical Function short form (HOOS-PS) (scored 0 to 100 points; lower indicates better health), Knee Injury and Osteoarthritis Outcome Score-Physical Function short form (KOOS-PS) (scored 0 to 100 points; lower indicates better health), EuroQol 5-Dimension 5-level (EQ-5D-5L) (scored -0.661 to 1 points; higher indicates better health), and a 10-point VAS for pain (perceived pain in the joint under consideration for surgery within the past 7 days) (scored 0 to 10 points; lower indicates better health). The performance of derived thresholds is reported using the Youden index, sensitivity, specificity, F1 score, geometric mean as a measure of central tendency, and area under the receiver operating characteristic curve. MCIDs for the EQ-5D-5L were 0.2 for HA and 0.2 for KA, with a maximum of 1 point, where higher values represented better health-related quality of life. For the pain scale, they were -0.9 for HA and -0.7 for KA, of 10 points (maximum), where lower scores represent lower pain. For the HOOS-PS, the MCID was -10, and for the KOOS-PS it was -5 of 100 points, where lower scores represent better functioning. Patients who reached the MCID differed from patients who did not reach the MCID with respect to baseline PROM scores across the evaluated PROMs and for both HA and KA. Patients who reached an MCID versus those who did not also differed regarding other aspects including education and comorbidities, but this was not consistent across PROMs and arthroplasty type. Preoperative PROM score thresholds for HA were 0.7 for EQ-5D-5L (Youden index: 0.55), 42 for HOOS-PS (Youden index: 0.27), and 3.5 for the pain scale (Youden index: 0.47). For KA, the thresholds were 0.6 for EQ-5D-5L (Youden index: 0.57), 39 for KOOS-PS (Youden index: 0.25), and 6.5 for the pain scale (Youden index: 0.40). A higher Youden index for EQ-5D-5L than for the other PROMs indicates that the thresholds for EQ-5D-5L were better for distinguishing patients who reached a meaningful improvement from those who did not. Patients who did not reach the thresholds could still achieve MCIDs, especially for functionality and the pain scale. We found that patients who experienced meaningful improvements (MCIDs) mainly differed from those who did not regarding their preoperative PROM scores. We further identified that patients undergoing HA or KA with a score above 0.7 or 0.6, respectively, on the EQ-5D-5L, below 42 or 39 on the HOOS-PS or KOOS-PS, or below 3.5 or 6.5 on a 10-point joint-specific pain scale presurgery had no meaningful benefit from surgery. The thresholds can support clinical decision-making. For example, when thresholds indicate that a meaningful improvement is not likely to be achieved after surgery, other treatment options may be prioritized. Although the thresholds can be used as support, patient preferences and medical expertise must supplement the decision. Future studies might evaluate the utility of using these thresholds in practice, examine how different thresholds can be combined as a multidimensional decision tool, and derive presurgery thresholds based on additional PROMs used in practice. Preoperative PROM score thresholds in this study will support clinicians in decision-making through objective measures that can improve the quality of the recommendation for surgery.